A Total production systems study on Four Aces Company - Castillo, Kermin Amor T. (College of Engineering, 1996)
This paper is a total production systems study of Four Aces, a small-scale company that distributes ice cream products such as pinipig, ice buko and ice cream sticks. The study has documented and analyzed the current production system for all products of the company. The following major problem areas have been identified: 1. Inaccurate forecasting methods 2.Inaccurate determination of capacity 3.Presence of idle time of workers and backlog of work-in-process 4.lack of efficient scheduling for operations 5.inadequate production planning 6.Inadequate implementation of quality policies. To answer these problems, this study will deliver the following: 1.Forecast for the year 1996, 2.Determination of capacity and capacity utilization 3.Line balancing and operations scheduling for the system 4.Monthly production plans 5.Standardization of work methods 6.Formulation and implementation of quality policies and training. These proposals have been formulated while taking into consideration the constraints of the company, the production system, the product and even of the study itself.